(untitled) (Trabalho & Educação, 2016)
This study aimed to investigate the perceptions of the teachers in relation to the contribution of the Course of Graduation in Engineering on the formation and development of the professional competencies of the students. This work was developed on the conceptions of competencies that had directed its theoretical and methodological basis. The research used the quantitative and qualitative approaches configuring itself a triangulation between methods. For the collection of the quantitative data on model of competencies of Fleury and Fleury (2004) and the National Curricular Lines of the course of Graduation in Engineering were used structured questionnaires in accordance with. The analysis of these data involved 57 teachers who teach in the graduation in engineering. And then 12 interviews had been carried through in order to complement the information of the questionnaires. From the results it became possible to infer the perceptions of the teachers in relation to the contribution that the course provides in the professional formation of the academics and what the faculty members consider what is an institution of ideal education. ___ Este estudo teve como objetivo investigar as percepções dos docentes em relação à contribuição do Curso de Graduação em Engenharia, na formação e no desenvolvimento das competências profissionais dos discentes. O trabalho se desenvolveu baseado nas concepções de competência que direcionaram a sua fundamentação teórica e metodológica. A pesquisa utilizou as abordagens quantitativa e qualitativa configurando-se em uma triangulação entre métodos. Para a coleta dos dados quantitativos foram utilizados questionários estruturados de acordo com o modelo de competências de Fleury e Fleury (2004) e itens ligados às Diretrizes Curriculares Nacionais do curso de Graduação em Engenharia. A análise desses dados envolveu 57 docentes que lecionam na graduação em engenharia. Em sequência foram realizadas 12 entrevistas que complementaram as informações advindas dos questionários. A partir dos resultados fez-se possível inferir as percepções dos docentes em relação à contribuição que o curso proporciona na formação profissional dos acadêmicos e o que o corpo docente considera que seja uma instituição de ensino ideal.